Moving beyond chemotherapy in the management of follicular lymphoma (Canadian Hematology Today, 2022)
Follicular lymphoma (FL) is the most common indolent lymphoma. It is estimated that approximately 2,000 Canadians are newly diagnosed with FL each year; however, this is an underestimation of the disease burden due to the indolent nature of FL. Indeed, the life expectancy for most patients can be measured in decades, with slow but constant improvement in survival estimates having been achieved over time.Traditionally, FL has been considered a chemo-sensitive disease and, for the last 15 years, antibodies targeting the CD20 surface epitope on B cells have become a compelling adjunct to induce long-lasting remission in the frontline setting. Outcomes are favourable for most patients; a long-term follow-up from the seminal PRIMA trial showed that the median progression-free survival (PFS) was 10.5 years in patients treated with immunochemotherapy as part of an initial induction regimen followed by rituximab maintenance, as compared with just over 4 years in the control arm (initial induction regimen followed by observation). In terms of chemotherapy backbone, bendamustine has established itself as the preferred standard in Canada and induces durable response in the majority of patients.This article will focus on patients with high-tumour burden disease in need of treatment, as opposed to patients with limited-stage disease who may benefit from localized radiation or patients with advanced-stage with low-tumour burden disease who may benefit from observation or single agent rituximab.